Multicolor Two-Photon Microscopy Imaging of Lipid Droplets and Liver Capsule Macrophages In Vivo - Kim, Eun Seo; Lee, Jeong Mi; Kwak, Jong Young; Lee, Hyo Won; Lee, In Jeong; Kim, Hwan Myung (Analytical Chemistry, 2024)
Lipid droplets (LDs) store energy and supply fatty acids and cholesterol. LDs are a hallmark of chronic nonalcoholic fatty liver disease (NAFLD). Recently, studies have focused on the role of hepatic macrophages in NAFLD. Green fluorescent protein (GFP) is used for labeling the characteristic targets in bioimaging analysis. Cx3cr1-GFP mice are widely used in studying the liver macrophages such as the NAFLD model. Here, we have developed a tool for two-photon microscopic observation to study the interactions between LDs labeled with LD2 and liver capsule macrophages labeled with GFP in vivo. LD2, a small-molecule two-photon excitation fluorescent probe for LDs, exhibits deep-red (700 nm) fluorescence upon excitation at 880 nm, high cell staining ability and photostability, and low cytotoxicity. This probe can clearly observe LDs through two-photon microscopy (TPM) and enables the simultaneous imaging of GFP+ liver capsule macrophages (LCMs) in vivo in the liver capsule of Cx3cr1-GFP mice. In the NAFLD mouse model, Cx3cr1+ LCMs and LDs increased with the progress of fatty liver disease, and spatiotemporal changes in LCMs were observed through intravital 3D TPM images. LD2 will aid in studying the interactions and immunological roles of hepatic macrophages and LDs to better understand NAFLD.
Keywords: Chronic nonalcoholic fatty liver disease; Energy; Green fluorescent protein; In-vivo; Lipid droplets; Liver capsule; Microscopy imaging; Multi-colors; Non-alcoholic fatty liver disease; Two photon microscopy